Features of Breast Cancer in Women under 50 Years of Age in HIV Positive and Negative Patients in Limpopo Province, South Africa - Mirza Mohamod Zahir Uddin Bhuiyan (Medical Science: Recent Advances and Applications Vol. 2, 2025)
Background: Breast cancer and HIV are major global burden of disease among women. There are 39.9 million people globally living with HIV in 2023 and 53% of which were women and girls. Breast cancer is the most diagnosed cancer in women and incidence with 2.3 million comprising 11.6% of all cancer cases in 2022. Breast cancer is commonly occurring in elderly women in Europe and America. However, in Africa, it happens often among younger women. Objective: Primary objective of the study is to better understand the features of breast cancer (stage, hormonal status, grading and molecular subtype) in women under 50 years and to identify any differences between HIV-positive and negative groups of breast cancer patients. Methods: A retrospective descriptive quantitative study was designed to analyse the profile of women under 50 years old with breast cancers who attended Mankweng Breast Oncology Clinic from July 2020 to December 2021. Mankweng Breast Cancer Clinic register was used to get patients’ initial data, and the patients’ relevant records were assessed to collect detailed information. The statistical software package SPSS v29 was used for data analysis. Results: A total of 109 breast cancer patients were evaluated. The mean age was 40.6 years among HIV-negative patients and 39 years among HIV-positive patients. Regarding HIV status, 28 patients (25.7%) were HIV-positive, while 81 patients (74.3%) were HIV-negative. In the HIV-positive group, the distribution of molecular subtypes was as follows: Luminal A in 5 patients (24%), Luminal B in 8 patients (38%), HER2+ overexpression in 3 patients (14%), and Triple Negative in 5 patients (24%). Regarding disease stage, 6 patients (21%) were diagnosed at an early stage, while 22 patients (79%) presented with late-stage disease. Among the HIV-negative group, the molecular subtypes were distributed as follows: Luminal A in 16 patients (22%), Luminal B in 41 patients (58%), HER2+ overexpression in 7 patients (10%), and Triple Negative in 7 patients (10%). Regarding disease stage, 16 patients (20%) were diagnosed at an early stage, while 65 patients (80%) presented with late-stage breast cancer. Regarding the histological type of breast cancer in this study, all patients both HIV-positive and HIV-negative patients had Invasive ductal carcinoma (no special type). Conclusion: Mean age of breast cancer in HIV-positive women is slightly younger than HIV-negative. Triple negative molecular subtype was proportionately more in the HIV-positive group in comparison to HIV-negative patients. Majority of breast cancer patients presented in an advanced stage in both HIV-positive and negative groups. Initiative of Routine breast cancer screening should take place on this population of women under 40-year age.